Kedudukan Hukum Menteri Triumvirat dalam Sistem Ketatanegaraan Republik Indonesia - Renaldo Lutu; Saryono Yohanes; Hernimus Ratu Udju (Hakim, 2024)
The purpose of this study is to analyze the legal position of the Minister of Ttriumvirat in the Constitutional system of the Republic of Indonesia. This research method is normative law (library research), this research examines legal materials, books, and laws and regulations that are closely related to the legal issues studied. The results showed that the legal position of the triumvirate minister as the executor of the Presidential duties in the constitutional system of the Republic of Indonesia is specifically regulated in the constitution of the Republic of Indonesia, namely contained in article 8 paragraph 3 and also in the hierarchy of laws and regulations in MPR Decree Number VII / MPR / 1973, precisely article 5 as the basis for legitimacy and recommendations in terms of filling the vacancy of the office of president and vice president. The basis for considering the Triumvirate Minister as the executor of Presidential duties if the president and / or vice president quits in the middle of his term of office is because they are considered to understand the course of government and have responsibility for foreign policy, domestic government, and national defense.